Full-scale evaluation of fire-resistant building integrated photovoltaic systems with different installation positions of junction boxes. Issue 9 (November 2018) - Huang, Yen-Chieh; Lee, Shin-Ku; Chan, Chi-Chang; Wang, Shui-Jinn
Building integrated photovoltaic (BIPV) systems are a promising strategy to integrate photovoltaic (PV) systems with building materials to reduce construction costs and add aesthetic features. In this study, a fire test in accordance with ISO 834-1:1999, CNS 14803-2010 and ISO 3008:2007 to provide the standard heating curve was carried out to investigate the fire-resistant characteristics based on the breaking behaviour and surface temperature distribution of type I and type II BIPV modules. The BIPV modules tested have both open and hidden junction-box (J-box) designs, with the aim of reducing fire risks. Our results show that the proposed type II BIPV module could resist the simulated room fire test for about 12 min without reducing any risk with regard to the J-box. Furthermore, the type II BIPV module could resist a fire test at temperatures of up to ∼1000℃ for 60 min with better compartment functionality when refractory glasses are employed. The BIPV fire test data reported in this study can help to improve the design and development of BIPV systems.